Additive manufacturing of bio-inspired multi-scale hierarchically strengthened lattice structures. (August 2021) - Tan, Chaolin; Zou, Ji; Li, Sheng; Jamshidi, Parastoo; Abena, Alessandro; Forsey, Alex; Moat, Richard J.; Essa, Khamis; Wang, Minshi; Zhou, Kesong; Attallah, Moataz M.
Abstract: The next-generation medical implants require locally customised biomechanical behaviour to echo the properties of hard tissues, making additive manufacturing (AM) an ideal route due to its superior manufacturing flexibility. AM of titanium alloys with designed porosity is the mainstream for artificial implants, which, however, hardly balance the strength-modulus combination. Here a martensitic TiNi biomaterial with low modulus and asymmetric mechanical behaviour that mimics human bones is explored. TiNi functionally graded lattice structure (FGLS) is bio-inspired by bone architecture and processed by AM. Bio-inspired FGLS shows much higher strength and ductility than the uniform lattice despite having an equivalent structural porosity. Post-process heat-treatments alter the microstructure and result in a multi-scale hierarchically strengthened behaviour in FGLS, offering one of the highest specific strengths (about 70 kN m/kg) among porous biometals, while keeping a low specific modulus and reasonable ductility. Besides, the deformation behaviour of FGLS is in-situ monitored, which, together with microscopic observations, reveal a multi-scale failure mechanism. The bio-inspired FGLS shows better biomechanical compatibility than the uniform lattice, including density, tension/compression asymmetry, modulus, and strength. The findings highlight the ability of AM in tailoring a modulus-strength-ductility trade-off through bio-inspired multi-scale hierarchical structure design. Graphical abstract: Image 1 Highlights: Mechanically asymmetric martensitic TiNi echoes bone mechanical behaviour. Bio-inspired functionally graded lattices can mimic natural bone properties. Graded lattice achieves an ultrahigh specific strength among porous biometals. A multi-scale hierarchical microstructure created unique properties.